Pharmaceutical care for the elderly: a study with academics from the University of Maturity of Gurupi – Unirg (Research, Society and Development, 2023)
Aging is a natural event for everyone. With increasing age, the frequency of medication uses increases, and many elderly people end up taking four or more medications at the same time. The high incidence of polypharmacy in the elderly is directly related to the increased risk of drug interactions and adverse drug reactions. The aim of this study was to analyze drug consumption patterns, their relationship with socioeconomic aspects and self-knowledge about their health and drug treatment among the elderly enrolled at the Universidad da Maturity of Gurupi-UMG. This is a descriptive exploratory study, in which a questionnaire was applied with data analyzed using descriptive statistics. The result of the research has a total of 15 elderly people interviewed, 14 women (93%) and 1 man (7%), the prevalence of females demonstrates that they seek a better quality of life. In the analysis of the data, 93% were diagnosed with some condition resulting from aging, with arterial hypertension present in (73%) of the cases, and one of the causes of reduced expectation and quality of life of individuals, which can lead to a series of other chronic degenerative diseases resulting in the consumption of various drugs, which requires careful pharmaceutical attention. The pharmacist is increasingly qualified to care for the elderly population, avoiding problems related to medication, ensuring the success of pharmacotherapy and resulting in a better quality of life.